The forces behind social unrest: Evidence from the Covid-19 pandemic - Mario Lackner; Uwe Sunde; Rudolf Winter-Ebmer (Johannes Kepler University of Linz, Department of Economics, 2023)
Despite growing concerns about the erosion of social cohesion and intensified social unrest as consequence of increasing economic and emotional stress, evidence for such a link is still lacking. We use a unique combination of nationally representative survey data, event data on social unrest, and data on Covid-19 fatalities and unemployment at a weekly resolution to investigate the emotional forces behind social unrest in the context of the pandemic in the USA. The results show that pandemic-related unemployment and Covid19 fatalities intensified negative emotional stress and led to a deterioration of economic confidence among individuals. The prevalence of negative emotional stress, particularly in economically strained and politically polarized environments, was, in turn, associated with intensified social unrest as measured by political protests. No such link is found for economic perceptions
Keywords: 330